A dataset of daily ambulatory psychological and physiological recording for emotion research - Xinyu Shui (Scientific Data, 2021)
Measurement(s) Heart Rate • Galvanic Skin Response • Emotion Technology Type(s) photoplethysmography • Surface Electrode • Day Reconstruction Method • Experience Sampling Method Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13803185